2007
DOI: 10.1038/sj.emboj.7601871
|View full text |Cite
|
Sign up to set email alerts
|

Organization of sister origins and replisomes during multifork DNA replication in Escherichia coli

Abstract: The replication period of Escherichia coli cells grown in rich medium lasts longer than one generation. Initiation thus occurs in the 'mother-' or 'grandmother generation'. Sister origins in such cells were found to be colocalized for an entire generation or more, whereas sister origins in slow-growing cells were colocalized for about 0.1-0.2 generations. The role of origin inactivation (sequestration) by the SeqA protein in origin colocalization was studied by comparing sequestration-deficient mutants with wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 41 publications
7
103
1
1
Order By: Relevance
“…6b). In our experiments, initiation of DNA replication in the mother cell before cytokinesis cannot be attributed to multifork replication [26][27][28] because we never observe a new round of DNA replication to initiate until the previous round has finished.…”
Section: Resultsmentioning
confidence: 88%
“…6b). In our experiments, initiation of DNA replication in the mother cell before cytokinesis cannot be attributed to multifork replication [26][27][28] because we never observe a new round of DNA replication to initiate until the previous round has finished.…”
Section: Resultsmentioning
confidence: 88%
“…Further co-localization of replication forks during segregation of multi-fork chromosomes In E. coli it has been found that the SeqA protein may be involved in the organization of new DNA at the replication forks (Fossum et al, 2007;Hiraga et al, 1998;Molina & Skarstad, 2004). The structures formed by SeqA are largely independent of the exact numbers of replication forks, and seem to be present in numbers roughly proportional to cell size Odsbu et al, 2009).…”
Section: Simultaneous Replication Of Two Copies Of Chriimentioning
confidence: 99%
“…Three and four oriII foci have been observed in another similar microscopy study of LB-grown cells (Saint-Dic et al, 2008), supporting our result. Also, in E. coli, both separate and co-localized origins have been observed in the same cell (giving the unexpected number of three foci), depending on the growth conditions (Adachi et al, 2008;Fossum et al, 2007;Nielsen et al, 2007).…”
Section: Simultaneous Replication Of Two Copies Of Chriimentioning
confidence: 99%
See 1 more Smart Citation
“…or fluorescently tagged SeqA protein (Brendler et al, 2000;Fossum et al, 2007;Hiraga et al, 1998;Molina & Skarstad, 2004;Onogi et al, 1999;Yamazoe et al, 2005). Formation of such SeqA foci depends on ongoing replication (Hiraga et al, 2000).…”
Section: Localization Of Replication Forks Is Changed During Compactionmentioning
confidence: 99%